(untitled) (Visioner : Jurnal Manajemen dan Bisnis, 2025)
Kabupaten Passer is one area that has more villages than other districts, where the economy that occurs in the community is more simple. The economic potential of the Paser Regency, which is based on agricultural products and coal mining, makes the economy of the village community increase. On September 9, 2015, President of the Republic of Indonesia Joko Widodo was accompanied by OJK Chairman Muliaman D Hadad, BI Governor Agus Martowardojo, Coordinating Minister for Economic Affairs Darmin Nasution, ESDM Minister Sudirman Said, Minister of Finance Bambang Brodjonegoro, Minister of Agriculture Amran Sulaiman, Minister of Trade Thomas Lembong, Minister of Secretary Negara Pratikno, and Cabinet Secretary Pramono Anung, announced the Economic Policy Package September 1. The formulation of the research problem was formulated as follows:1. Does Debt to Equity Ratio, Cash Ratio and Current Ratio significantly influence the Profitability of BUMDes Amanah in Padang Jaya Village, Kec. Kuaro District Paser Period January to December 2016? 2. Which of the Debt to Equity Ratio, Cash Ratio and Current Ratio has a significant effect on profitability partially influential on Profitability at BUMDes Amanah in Padang Jaya Village Kec. Kuaro District Paser Period January to December 2016 hasil analisis untuk persamaan regresi linier berganda sebagai berikut : Y = b0+b1X1+b2X2+b3X3 dimana hasil perhitungan dengan persamaan Y = 13,146+ 44,377X1 + 4,046X2 + 7,290X3 terdapat pengaruh antara seluruh variabel independen Struktur Modal-DER (X1), Likuiditas-Rasio Lancar (X2) dan Likuiditas-Rasio Perputaran Kas (X3) terhadap variabel dependen Profitabilitas-ROE (Y) secara simultan. Secara parsial variabel Likuiditas-Rasio Lancar (X2) terhadap Profitabilitas-ROE (Y) menunjukan nilai t hitung sebesar 5,671 lebih besar daripada t tabel 2,262 dengan nilai sig 0,000 lebih kecil dari nilai α = 5%. Hal ini menunjukan bahwa variabel Likuiditas-Rasio Lancar (X2) secara parsial paling berpengaruh terhadap Profitabilitas-ROE (Y)